Gambaran Faktor-Faktor Penyebab Terjadinya Perilaku Bullying pada Anak: Overview of Factors Causing the Occurrence of Bullying Behavior in Children - Novi Herawati; Deharnita (NERS Jurnal Keperawatan, 2019)
Bullying is the child's aggressive behavior repeatedly towards his friend which causes the victim. Factors causing bullying behavior at school include personality factors, interpersonal communication of children with their parents (parenting), the role of peer groups and school climate. Descriptive research, aimed at knowing the description of the factors causing bullying behavior in children in SMPN 2 Solok City in 2018. The sampling technique is simple random, with a sample of 79 people. Data collection was carried out May 22-28, 2018. Analysis was carried out univariately and presented with a frequency distribution table. The results showed more part (70.9%) of respondents did physical forms of bullying in the form of hitting, more partially (58.2%) verbally in the form of dubbing, more in part (78.5%) mentally in the form of silence (not care about). Most of the causes of bullying behavior from family factors (82.3%) were due to seeing a commotion at home, from the school factor that was partially less (46.8%) the school ignored problems between schools, from the peer factor mostly (77.2%) because peers liked to taunt others friend. Schools especially counseling teachers are expected to give special attention to student behavior at school to prevent bullying from happening at school.